Application of modern methods (with special reference to planning, programming, budgeting techniques) to the choice of investment projects (Paris : European Conference of Ministers of Transport, 1971)
The publication outlines that full implementation of a P. P. B. (Planning, Programming, Budgeting) system would involve improvements, not only in evaluation procedures but also in forecasting and speculating about the future, in devising measures of achievement and improving the data available to analysts.
ne 28/02/2018
Loan
Keywords: Transportation; Program Budgeting